2021
DOI: 10.1021/acs.chemrev.1c00574
|View full text |Cite
|
Sign up to set email alerts
|

Shortening Synthetic Routes to Small Molecule Active Pharmaceutical Ingredients Employing Biocatalytic Methods

Abstract: Biocatalysis, using enzymes for organic synthesis, has emerged as powerful tool for the synthesis of active pharmaceutical ingredients (APIs). The first industrial biocatalytic processes launched in the first half of the last century exploited whole-cell microorganisms where the specific enzyme at work was not known. In the meantime, novel molecular biology methods, such as efficient gene sequencing and synthesis, triggered breakthroughs in directed evolution for the rapid development of process-stable enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 583 publications
0
76
0
1
Order By: Relevance
“…Proline hydroxylases (PHs) represent well-studied and characterised Fe/αKGs for free amino acid hydroxyl functionalisation. Hüttel and Klein applied PHs for the selective hydroxylation of L-proline (17) and its congener L-pipecolic acid (18) (L-Pip), yielding building blocks for pharmaceutical synthesis. [111] The authors fed L-proline to growing cultures of cis-P3H, cis-P4H and trans-P4H in E. coli strains to produce the respective hydroxyprolines (Hyps) in isolated yields of 35-61 % after purification via ion-exchange chromatography.…”
Section: Iron-and α-Ketoglutarate-dependent Oxygenasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline hydroxylases (PHs) represent well-studied and characterised Fe/αKGs for free amino acid hydroxyl functionalisation. Hüttel and Klein applied PHs for the selective hydroxylation of L-proline (17) and its congener L-pipecolic acid (18) (L-Pip), yielding building blocks for pharmaceutical synthesis. [111] The authors fed L-proline to growing cultures of cis-P3H, cis-P4H and trans-P4H in E. coli strains to produce the respective hydroxyprolines (Hyps) in isolated yields of 35-61 % after purification via ion-exchange chromatography.…”
Section: Iron-and α-Ketoglutarate-dependent Oxygenasesmentioning
confidence: 99%
“…Many reviews have highlighted the benefit of biocatalysis to the pharmaceutical industry. [15][16][17][18] Selective (sp 3 or sp 2 ) CÀ H oxyfunctionalisation currently represents one of the most challenging reactions in organic chemistry. [19] Biocatalysts have been increasingly utilised to address this organic synthesis challenge, enabling high selectivity that chemical catalysis may fall short.…”
Section: Introductionmentioning
confidence: 99%
“…Through retrieval, it was found that the current stability and catalytic efficiency of specific enzymes have not yet reached the requirements of mature process conditions. In view of these situations, in addition to the use of computer-aided analysis of candidate enzymes in the protein database and reasonable and reliable prediction of their substrate specificity and activity, modern protein engineering tools can also be used to directly introduce the required characteristics into the target site to synthesize suitable new enzymes [ 152 ]. These technologies benefit from the application of artificial intelligence and high-throughput sequencing and screening technologies.…”
Section: Design and Modification Of Enzymementioning
confidence: 99%
“…4,5 Akin to photocatalysis, biocatalysis has been shown to enable sustainable reaction methodologies due to its generally mild reaction conditions, use of aqueous media, high stereo-and chemoselectivity, and ever-increasing substrate and reaction scope. [6][7][8][9][10][11][12][13] At the interface of these two fields of catalysis, photobiocatalysis arose, whereby either the enzyme itself requires light (naturally or by promiscuity) or photoinduced electrons are transferred to it. [14][15][16][17] The scope of photobiocatalytic transformations was significantly expanded following the discovery of fatty-acid photodecarboxylases in 2017.…”
Section: Introductionmentioning
confidence: 99%